Limb reduction defects in the northern region of England 1985-92. Issue 3 (June 1995) - Wright, M J; Newell, J N; Charlton, M E; Hey, E N; Donaldson, L J; Burn, J
Abstract : STUDY OBJECTIVE--To test the hypothesis that children born to mothers living near the sea are at increased risk of limb reduction defects. DESIGN--Descriptive data analysis. SETTING--The northern health region of England. PATIENTS--All children born between 1 January 1985 and 31 December 1992 in the northern region of England with isolated limb reduction defects. MAIN RESULTS--The birth prevalence of isolated limb reduction defects was not affected by the distance the mother lived from the sea. There was some evidence of space-time clustering, but there was no evidence of statistically significant variation in the occurrence of the condition with sex, time of birth (monthly or yearly), or county of birth. CONCLUSIONS--There is no evidence that children born to mothers living near the sea are at increased risk of limb reduction defects.